2013
DOI: 10.1039/c2cs35284b
|View full text |Cite
|
Sign up to set email alerts
|

Peptides and peptidomimetics that behave as low molecular weight gelators

Abstract: Gelators may be divided into chemical gels and physical gels: the internal structure of chemical gels is made of chemical bonds, while physical gels are characterized by dynamic cross-links that are constantly created and broken. The gelator present in physical gels may be an inorganic or an organic compound, the latter having a molecular weight of ≤500 amu. These compounds are generally called "low molecular weight gelators" (LMWGs). In this tutorial review we want to focus our attention on short peptides or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
194
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 281 publications
(195 citation statements)
references
References 59 publications
1
194
0
Order By: Relevance
“…Zhang introduced the concept of "Peptide Lego" to classify EAK16 and similar ionic selfcomplementary peptides. 10 Based on this pioneering work, 2 , and demonstrated that it also serves as starting point for playing 'Peptide Lego', i.e. they observed that many analogues of (3) formed brillar hydrogels, whereby nonaromatic peptides formed weaker gels than aromatic analogues.…”
Section: Introductionmentioning
confidence: 97%
“…Zhang introduced the concept of "Peptide Lego" to classify EAK16 and similar ionic selfcomplementary peptides. 10 Based on this pioneering work, 2 , and demonstrated that it also serves as starting point for playing 'Peptide Lego', i.e. they observed that many analogues of (3) formed brillar hydrogels, whereby nonaromatic peptides formed weaker gels than aromatic analogues.…”
Section: Introductionmentioning
confidence: 97%
“…Formation of organogel from the DPH 2 molecule will be beneficial for the enhancement of the curcumin fluorescence because it can exploit both the photosensitizing property of DPH and the solvent polarity of the organogel. This cooperative effect was observed in some photoluminescent organogels that were prepared from pseudo-peptidic gelator molecules [11,12].…”
Section: Introductionmentioning
confidence: 86%
“…1,2 A recent expansion in the number of LMWG systems reported has led to a rapid growth in reports of characterisation and applications of a particular class of this type of molecule, namely aromatic conjugated dipeptide LMWG. [3][4][5][6][7][8] These systems typically consist of a hydrophobic, often aromatic, dipeptide sequences conjugated to Fmoc (9-fluorenylmethoxycarbonyl) 9,10 or naphthalene 3,4 ; further conjugations have also been reported. 11,12 Through the use of an environmental cue, 13 such as an enzymatic trigger, 14 temperature, 15,16 or light 12 some of these conjugates selfassemble into anisotropic fibrils that can eventually cause hydrogelation through the immobilisation of water by the fibrillar network.…”
Section: Introductionmentioning
confidence: 99%